Empowering music education with technology: a bibliometric perspective - Yidi Ma; Chengliang Wang (Humanities & Social Sciences Communications)
Abstract As technology becomes an integral part of educational content and methodology, its research significance continues to grow, particularly in the relationship between music and technology. The primary aim of this study is to quantify and analyze academic research outcomes concerning the use of technology in music education. The selected sample is drawn from the WoS core database, encompassing academic achievements from 1991 to 2024. Various bibliometric software tools and three major laws were employed for the analysis, examining publication distribution, relevant journals and authors, research countries, keywords, and current and future research themes. Presently, research is mainly focused on four themes: technology integration and interaction, adaptive learning and creative teaching methods, educational frameworks and performance, and the diverse inclusion of children and adolescents. Looking ahead, the two frontier hot topics in this field are remote and online education, and innovation in higher education and educational models. This study aims to contribute to the comprehensive bibliometric analysis literature on the use of technology in music education.